The Faster-Onset Antidepressant Effects of Hypidone Hydrochloride (YL-0919) in Monkeys Subjected to Chronic Unpredictable Stress - Yin, Yong-Yu; Tian, Chao-Yang; Fang, Xin-Xin; Shang, Chao; Zhang, Li-Ming; Xu, Qiang; Li, Yun-Feng (Frontiers in Pharmacology, 2020)
Given the limited monkey models of depression available to date, as well as the procedural complexity and time investments that they involve, the ability to test the efficacy and time course of antidepressants in monkey models is greatly restricted. The present study attempted to build a simple and feasible monkey model of depression with chronic unpredictable stress (CUS) and evaluate the antidepressant effect and onset time of fluoxetine hydrochloride (FLX) and the new drug hypidone hydrochloride (YL-0919), a potent and selective 5-HT reuptake inhibitor, 5-HT1A receptor partial agonist and 5-HT6 receptor full agonist. Female cynomolgus monkeys with low social status in their colonies were selected and subjected to CUS for 8 weeks by means of food and water deprivation, space restriction, loud noise, strobe light, and intimidation with fake snakes. Huddling, self-clasping, locomotion and environmental exploration were monitored to evaluate behavioral changes. In addition, the window-opening test was used to evaluate the exploratory interest of the monkeys. The present results revealed that CUS-exposed monkeys displayed significant depression-like behaviors, including significant decreases in exploratory interest, locomotion, and exploration as well as significant increases in huddling and self-clasping behavior and the level of fecal cortisol after 8 weeks of CUS. Treatment with FLX (2.4 mg/kg, i.g.) or YL-0919 (1.2 mg/kg, i.g.) markedly reversed the depression-like behaviors caused by CUS, producing significant antidepressant effects. YL-0919 (once daily for 9 days) had a faster-onset antidepressant effect, compared with FLX (once daily for 17 days). In summary, the present study first established a CUS model using female cynomolgus monkeys with low social status and then successfully evaluated the onset time of 5-HTergic antidepressants. The results suggested that monkeys exposed to CUS displayed significant depression-like behaviors, and both FLX and YL-0919 produced antidepressant effects in this model. Moreover, YL-0919 appeared to act faster than FLX. The present study provides a promising prospect for the evaluation of fast-onset antidepressant drugs based on a CUS monkey model.